Lipidomic Landscapes of Cryopreserved Sperm from Alpine and Spanish–Creole Bucks - Mustafa Bodu; Mustafa Hitit; Selamawit Woldesenbet; Muhammet Raşit Uğur; Zeynep Erdoğan; Olivia Chika Greenwood; Raheem Davian Murray; Andres Pech Cervantes; Erdoğan Memili (Animals)
This study provides a comparative analysis of the post-thaw sperm lipidomic profiles of Alpine and Spanish–Creole goat breeds to explore breed-specific differences in fatty acid composition and their implications for sperm function and reproductive efficiency. Lipids were extracted from cryopreserved semen samples of Alpine (n = 7) and Spanish–Creole (n = 4) mature bucks and subsequently analyzed by gas chromatography–mass spectrometry (GC-MS), with 21 fatty acids identified within the two breeds. Eight of these fatty acids, namely 13:0, 16:0, 18:0, 24:0, 14:1, 18:1 (cis-9), 24:1, and 18:2 showed significant differences (p < 0.05). The levels of 16:0, 18:0, 24:0, 18:1 (cis-9), 18:1, and 18:2 were higher in the Alpine breed, whereas the levels of 13:0, 14:1, and 24:1 were higher in the Spanish–Creole breed (p < 0.05). Of those, 16:0, 18:1 (cis-9), and 18:2 were both statistically and biologically significant (p < 0.05, FC > 2). Concentrations of the total fatty acids, total saturated fatty acids (Total-SFA), and total polyunsaturated fatty acids (Total-PUFA) were significantly higher in the Alpine breed, whereas the concentrations of the total cis-monounsaturated fatty acid (Total cis-MUFA) were significantly higher in the Spanish–Creole breed (p < 0.05). Network and pathway analyses revealed that 16:0, 18:1 (cis-9), and 18:2 contributed to the most central nodes of the lipidomic network, which may support membrane stability and cryotolerance. The lipidomic differences observed between breeds may be attributed to both genetic and environmental factors and may provide valuable tools for enhancing breeding strategies, artificial insemination programs, and sperm cryopreservation techniques.